Conjectures. Logic and the Thomistic Debate on Human Freedom and the Divine Causality - Redmond, Walter (Metafísica y Persona, 2017)
In the question of human freedom, the theist is worse off than the non-believer. Both must explain how I can perform a free act in a physically determined universe. But the theist must also explain how I can act freely in a universe where God not only causes everything but also knows what I shall do. If the theist is a Christian, he has one more problem: he must reconcile human freedom not only with divine causality and omniscience (the philosophical problem), but with supernatural grace as well (the theological problem). I wish to reflect here only on the philosophical issue, which I think is fundamental to theological solutions.